Interest-rate pegs, central bank asset purchases and the reversal puzzle - Rafael Gerke; Sebastian Giesen; Daniel Kienzler; Jörn Tenhofen (Deutsche Bundesbank, 2017)
We analyze the macroeconomic implications of a transient interest-rate peg in combination with a QE program in a non-linear medium-scale DSGE model. In this context, we re-examine what has become known as the reversal puzzle (Carlstrom, Fuerst and Paustian, 2015) and provide an analytical explanation for its appearance. We show that the puzzle is intimately related with agents' expectations. If, for instance, agents do not anticipate the peg, the reversal does not appear. The same is true if agents' inflation expectations are influenced by a monetary authority which follows a price-level-targeting rule instead of a standard Taylor rule. In this case, sign reversals do not occur even for very long durations of pegged nominal interest rates.
Keywords: E32; E44; E52; E61; 330; Unconventional Monetary Policy; Interest-Rate Peg; Perfect Foresight; Reversal Puzzle; Price-Level Targeting